2005
DOI: 10.1007/bf03325881
|View full text |Cite
|
Sign up to set email alerts
|

Potassium induced salinity tolerance in wheat (Triticum aestivum L.)

Abstract: Water culture experiments were conducted to study the response of ten wheat genotypes to external K application (10 mmol KCI dm _ 3 ) at seedling stage under saline condition (0 and 100 mmol NaCl dm _ 3 ). The data showed that there was an increase in the shoot and root length with the application of external K. The increase was more pronounced under control than under saline conditions. The better performing genotypes under two treatments were Bhitai, NIAB-41, NIAB-I076 and Khirman. The enhanced growth of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
4
13
0
Order By: Relevance
“…Singh et al (2000) and Jatav et al (2012) have also found better growth and yield of wheat crop with the addition of potassium. Increase in root and shoot length as a result of application of potassium has been earlier reported in Triticum aestivum L. by Shirazi et al (2005) also. KNO 3 induced increase in fresh and dry weight has earlier been reported in sunflower (Helianthus annuus L.) and safflower (Carthamus tinctorius L.) by Jabeen and Ahmad (2011) as well.…”
Section: Resultssupporting
confidence: 61%
“…Singh et al (2000) and Jatav et al (2012) have also found better growth and yield of wheat crop with the addition of potassium. Increase in root and shoot length as a result of application of potassium has been earlier reported in Triticum aestivum L. by Shirazi et al (2005) also. KNO 3 induced increase in fresh and dry weight has earlier been reported in sunflower (Helianthus annuus L.) and safflower (Carthamus tinctorius L.) by Jabeen and Ahmad (2011) as well.…”
Section: Resultssupporting
confidence: 61%
“…C and HS refer to control and heat stress treatments, respectively. In our study, as reported by Bergmann (1992), at booting, the contents of K in the shoots varied between 26-53 mg/g (Table 3), eventually displaying a close interaction with Na (Shirazi et al, 2005). It was also found that, as a general pattern, the concentrations of K in the control genotypes, decreased during the growth cycle in all tissues.…”
Section: Resultssupporting
confidence: 88%
“…Electrical conductivity at SS-3 was significantly greater than the control in the first year and SS-2 and SS-3 were greater than the control in the second year. However, added salinity with sewage sludge and manure was not anywhere near the 7 mS cm −1 threshold for wheat (e.g., as reported by Shirazi et al 2005). Soil organic-matter content increased significantly with added sewage sludge (at SS-2, 40 Mg ha −1 , and SS-3, 60 Mg ha −1 ) compared to the control from the first year.…”
Section: Resultsmentioning
confidence: 54%